Fractal structure determines controlled release kinetics of monolithic osmotic pump tablets. (14th March 2013) - Yin, Xianzhen; Li, Haiyan; Liu, Ruihao; Chen, Jing; Ji, Junqiu; Chen, Jun; Shao, Qun; Xiao, Tiqiao; York, Peter; He, You; Zhang, Jiwen
Abstract Objectives To calculate the fractal dimension values of felodipine osmotic pump tablets during drug dissolution and to characterize the mechanism of the controlled drug release kinetics through three‐dimensional fractal data. Methods Three‐dimensional fractal values of volume (Df, volume) and surface (Df, surface) of the tablet core were calculated based on the box counting method. Key findings During the process of release of felodipine, both Df, volume and Df, surface were within the range of 2–3 and then changed markedly after a period of 3.0 h release, corresponding to extensive changes in entire shape, interior porous channels and surface structure of the tablet core. The curve of Df, volume mirrored that for tablet volume, however the curve of Df, surface was quite different from that of the surface area. Results showed that values of Df, surface correlated well with the drug release rate. Df, surface was found to be an efficient fractal parameter that could be used to characterize the complex changes to the tablet core that take place during drug release. Conclusions The fractal dimension can be used as a quantitative indicator reflecting the drug release performance and be regarded as a key indicator for the quality control of oral controlled drug delivery systems.